Exploring Gen Z Social Media Marketing Engagement on Brand Experience, Brand Equity, and Brand Trust: The Context of Muslim Fashion - Rahmawati; Nur Hidayati (Universitas Airlangga, 2023)
Objective: This research aims to analyze how social media marketing activities (SMMA) affect brand equity in Muslim fashion brands among Gen Z. Additionally, the study aims to determine the mediating role of brand experience and brand trust in the relationship between SMMA and brand equity. Design/Methods/Approach: The research participants were selected through purposive sampling based on the research objective. A total of 322 respondents who met the criteria were included in the study, and Smart PLS 3 software was used to test the hypotheses. Partial least squares (PLS) structural equation modeling was the analytical technique employed in this research. Findings: The findings indicate that social media marketing activities (SMMAs) are strongly linked to brand equity, brand experience, and brand trust. Moreover, both brand experience and brand trust are also significantly associated with brand equity. Brand experience and brand trust play a partial mediating role in the relationship between SMMAs and brand equity. Originality/Value: This research study offers several contributions to marketing literature and managerial implications. Firstly, the research findings can make a valuable addition to the existing marketing literature, particularly in consumer behavior in the digital era. Secondly, the study aims to examine the impact of brand experience and brand equity on customers' purchasing behavior in the Muslim fashion industry. Practical/Policy implication: It is recommended for marketers to manage social media pages, as these platforms facilitate the exchange of information and ideas among consumers. Effective management of social media pages can lead to positive outcomes and provide superior value and brand experience.